Inversion of the Bremmer Series (Journal of Computational Mathematics, 2018)
We consider the inverse backscattering problem for scalar waves in one dimension. We analyze the convergence of the inverse Bremmer series in this context and study its use in numerical simulations.
Keywords: Inverse scattering